Cascaded Symmetric Multilevel Inverter with Reduced Number of Controlled Switches - Tila Muhammad; Adnan Umar Khan; Hanif Jan; Muhammad Yasir Usman; Junaid Javed; Arsalan Aslam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Multilevel inverters have become popular among high power converters for the past few years due to their high quality output waveform and low total harmonic distortions (THD). In addition, the filter size also reduces significantly to achieve a pure sine wave output. Cascaded H-Bridge topology has been recognized as the most promising among various classical topologies for multi-level inverters on the basis of its modular form and ease of design, troubleshooting, packaging and high power capabilities. However, a large number of switches are required in cascaded H-Bridge multilevel inverter that leads to larger system losses and an increase in cost. In this paper the modified cascaded topology is proposed to reduce the number of controlled switches without affecting the resolution of output waveform or the number of voltage levels. We achieved this by replacing some of the high cost controlled transistor switches with diodes, in the cascaded H-Bridges. Furthermore, equal voltage source sharing is also possible by using the proposed topology. Hence the proposed inverter is a type of cascaded multilevel inverter with reduced switches, better modular structure, low cost and high efficiency. The inverter design is validated using simulations and tested on hardware prototype.